PENERAPAN MODEL TIME TOKEN ARENDS UNTUK MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN PKN SISWA KELAS IV SDN TUNJUNGTIRTO 02 - Susilowati, Susilowati (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The purpose of this research is to describe the application of Cooperative Time Token Arends learning model to increase learning outcomes of fourth grade students of SDN Tunjungtirto 02, Singosari. This research uses Classroom Action Research (PTK) with 2 (two) cycles. The subjects of this study were 16 students of grade IV SDN Tunjungtirto 02 Singosari. Data collection techniques in this study are observation, interviews, documentation, and tests. The technique to analyze the data used in this research is descriptive qualitative analysis technique. The results show that learning by applying the Time Token Arends Cooperative model on the subject of globalization can increase learning outcomes. Student learning outcomes also experienced an average increase from cycle I (72.12) to cycle II (76.9). Classical mastery increased by 12.5% from cycle I to cycle II.